2017
DOI: 10.1002/14651858.cd007289.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic chemotherapy for hydatidiform mole to prevent gestational trophoblastic neoplasia

Abstract: P-Chem may reduce the risk of progression to GTN in women with CMs who are at a high risk of malignant transformation; however, current evidence in favour of P-Chem is limited by the poor methodological quality and small size of the included studies. As P-Chem may increase drug resistance, delays treatment of GTN and may expose women toxic side effects, this practice cannot currently be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…A Cochrane database review (3 randomized controlled trials [RCTs], n5613) did not conclude sufficient evidence for standard administration of prophylactic chemotherapy to prevent postmolar GTN; however, evidence was suggestive that prophylactic chemotherapy may reduce the risk of progression to GTN among women with complete HM at high risk for malignant transformation. 15 The NCCN Guidelines state that prophylactic methotrexate or dactinomycin can be considered for patients deemed at high risk for postmolar GTN. Risk factors for postmolar GTN include age .40 years, hCG levels in excess of 100,000 mIU/mL, excessive uterine enlargement, and/or theca lutein cysts larger than 6 cm.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane database review (3 randomized controlled trials [RCTs], n5613) did not conclude sufficient evidence for standard administration of prophylactic chemotherapy to prevent postmolar GTN; however, evidence was suggestive that prophylactic chemotherapy may reduce the risk of progression to GTN among women with complete HM at high risk for malignant transformation. 15 The NCCN Guidelines state that prophylactic methotrexate or dactinomycin can be considered for patients deemed at high risk for postmolar GTN. Risk factors for postmolar GTN include age .40 years, hCG levels in excess of 100,000 mIU/mL, excessive uterine enlargement, and/or theca lutein cysts larger than 6 cm.…”
Section: Treatmentmentioning
confidence: 99%
“…Risk factors for postmolar GTN include age .40 years, hCG levels in excess of 100,000 mIU/mL, excessive uterine enlargement, and/or theca lutein cysts larger than 6 cm. 2,8,15,16 Follow-up Follow-up with hCG monitoring is essential after initial treatment of HM to ensure that hCG levels return to normal. The hCG molecules associated with GTD are more heterogenous and degraded than those associated with normal pregnancy.…”
Section: Treatmentmentioning
confidence: 99%
“…The analysis of almost 90 papers allowed to conclude that a prophylactic chemotherapy may decrease the risk of progression to GTN in women with complete mole pregnancy, in whose case there is a high risk of malignant transformation, yet the current evidence for the benefits of this therapy is quite limited by their low quality and a small number of patients in the analysed trials. Preventive chemotherapy may increase drug resistance, delay healing and cause side effects and that is why it cannot be routinely recommended and used [23]. Braga et al evaluated expectant versus immediate chemotherapy following pathological diagnosis of gestational choriocarcinoma in patients with nonmetastatic disease and concluded that close surveillance of women with pathological diagnosis of nonmetastatic gestational choriocarcinoma seems to be a safe practice [24].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…To reduce this malignant sequel, prophylactic single-agent chemotherapy after molar evacuation has been recommended for "highrisk" moles in patients having maternal age above 40 years [5]. However, Jiang et al and Geng et al have reported no significant decrease in postmolar GTN after prophylactic chemotherapy [6,7].…”
Section: Introductionmentioning
confidence: 99%